"MOTIRÕ – Um Modelo de Dificuldades com Informações de Awareness para Apoiar os Utilizadores e Desenvolvedores dos Fóruns Educacionais On-line - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
On-line discussion forums are asynchronous communication tools widely used in Learning Management Systems and are valuable tools for interconnecting groups and promoting reflection in learning through shared information. However, instructors and students face a variety of difficulties while interacting in forums. This thesis developed of a Difficulty Model in the context of educational on-line discussion forums to mitigate the needs faced by instructors and support collaborative learning. To support the Model, awareness information has also been investigated to help individuals interpret events, coordinate cooperative tasks, and anticipate needs. In addition, as a result of the research, it was possible to obtain data about the forums, such as benefits, strategies that instructors can adopt to have a more participatory forum, and improvements that can be explored and implemented as a way to enhance the forum tool. For this, we conducted an empirical study with instructors who work in distance learning and conducted a systematic mapping to identify results from the literature. The combination of these two studies allowed the creation of a Model of Difficulties called Motirõ. Motirõ is a Tupi-Guarani word that means get people together to build something, helping one another. The forum has this essence, it is a virtual space that brings people together to build and share knowledge through collaboration in which everyone grows together, helping one another. However, this essence has been lost in time and needs to be rescued. The Motirõ model aims to help the forum to be a usual tool, for this, we highlight the difficulties related to the forum and give a direction of what can be done to improve and enhance this tool. The difficulties model is a guide that can be widely explored by the distance learning community. The validation of the model took place through a third study: the survey, which demonstrated an excellent approval rate for the scenarios developed and presented. Thus, the main contribution of this thesis consists of empirical evidence and literature about difficulties and awareness elements for coordinating educational forums, consolidating them in a model. Besides that, the results provide improvements that can be applied based on the numerous difficulties identified. This data and analysis are relevant to the distance learning community and can help instructors, developers, and researchers in the use and improvement of forums.
MOTIRÕ - A Model of Forum Difficulties with Awareness Information to Support Users of On-line Discussion Forums
Keywords: Ambientes virtuais compartilhados; Realidade virtual na educação; Comunidades virtuais - Grupos de discussão pela Internet; CIENCIAS EXATAS E DA TERRA: CIENCIA DA COMPUTACAO; Fórum de discussão; Sistemas Gerenciadores de Aprendizagem; Elementos de awareness; Benefícios dos fóruns; Modelo de dificuldades